Odpowiedzi

2010-01-27T14:09:30+01:00
A) 3a-6
b) -4x-4y
c) 5x-5
d) -a+3a^ (a do kwadratu)
e) 7t-14s-7
f) a-2b+jedna druga
g) 2m^+3m
h) 6pr+15p^-3p
i) 2x^y -3xy^+5xy
1 5 1
Najlepsza Odpowiedź!
2010-01-27T14:09:39+01:00
A) 3(a-2)=3a-6
b) -4(x+y)=-4x-4y
c) -5(-x+1)=5x-5
d) -3a(jedna trzecia -a )=-a+3a(kwadrat)
e) (t-2s-1)*7=7t-14s-7
f) jedna druga (2a-4b+1)=a-2b+jedna druga
g) m(2m+3)=2m(kwadrat)+3m
h) 3p(2r+5p-1)=6pr+15p(kwadrat)-3p
i)xy(2x-3y+5)=2x(kwadrat)y-3xy(kwadrat)+5xy

*kwadrat= do potegi 2
2010-01-27T14:11:00+01:00
A) 3(a-2)=3a-6
b) -4(x+y)=-4x-4y
c) -5(-x+1)=5x-5
d) -3a(1/3 -a )=-a+3a²
e) (t-2s-1)*7=7t-14st-7
f) 1/2 (2a-4b+1)=a-2b +1/2
g) m(2m+3)=2m²+3m
h) 3p(2r+5p-1)=6pr+15p²-3p
i)xy(2x-3y+5)= 2x²y-3xy²+5xy

mam nadzieję że pomogłam
jakby co pisz na priv:P
1 5 1